The Financial Component of the Scientific Publication's Value Original article - P. I. Kasatkin; J. A. Kovalchuk; I. M. Stepnov (Moscow Polytechnic University, 2022)
Publication activity in modern society is presented as a driving force of scientific and technological development and as an indicator of university management reporting. The article is devoted to the study of approaches to determining the monetary value of a scientific publication, taking into account different behavior's motives of researchers and teachers in higher education as authors. The methodological basis of the study was formed by concepts of creating a public good and financial good, concepts of scientific productivity and academic remuneration, neoclassical and neoinstitutional economic theories, approaches to the implementation of state policy in the field of science and education in terms of stimulating scientific publications. Research methods: critical and comparative analysis, with the inclusion of three groups of methods: a) the study of direct and indirect authors' motives and traps in the publication of scientific papers; b) asset evaluation methods; c) a combination of socio-economic campaigns for monetary evaluation of the results of scientific research. Asset valuation approaches have been adapted to assess the scientific publication's value from the position of the author as a beneficiary. The theoretical and practical significance of the research lies in the contribution to the value dimension of scientific publications for their authors in the conditions of academic capitalism with potential opportunities to receive monetary income from the results of their research.